Smart logistics solutions for reducing food waste: A case of D Nipah Catering - Muhammad Hairie, Hanis; Fernando, Yudi (Penerbit Universiti Malaysia Pahang, 2024)
The food and beverage (F&B) business is faced with a huge challenge in the form of food waste, which has a negative impact on profitability, sustainability, and environmental conservation. In recent years, smart logistical solutions have emerged as a potentially successful strategy for addressing the critical problem of food waste in the F&B industry. This article presents an overview of the application of smart logistics in the context of reducing food waste. The paper has a specific focus on the integration of technologies related to the Internet of Things (IoT) and production planning strategies. It investigated the concept of smart logistics and its benefits to improve decision-making, enhance visibility, and optimise the procedures involved in supply chain management. The study also underlined the role played by IoT in providing real-time monitoring, data collecting, and analysis, all of which can help in identifying and reducing concerns related to food waste. Qualitative methodologies involving the 5-whys analysis were used in this study to identify the root cause of the problem. Additionally, the present study highlights the significance of efficient production planning in reducing the amount of goods that are produced in excess, improving inventory management, and ensuring that production is in line with consumer demand. The findings also highlight the significance of combining the IoT technology and production planning in small and medium-sized enterprises (SMEs) to improve the efficiency and efficacy of their efforts to reduce food waste.